Agir linguageiro em um projeto didático do gênero redação do ENEM: desenvolvimento das capacidades de linguagem na esfera escolar - Vargas, Rosana Souza de (2025)
Contemporary discussions on Portuguese Language (PL) teaching point to the need to seek methodologies aligned with socio-discursive practices for the development of students' literacy in basic education. In view of this, this research, inserted in the area of ​​Applied Linguistics, analyzed the written productions of a group of students in the 3rd year of High School (EM), based on the development of a Genre Didactic Project (PDG) (Guimarães; Kersch, 2012) anchored in Socio-Discursive Interactionism (ISD) (Bronckart, 2006), from the Geneva current. The central thesis of the study was that a PDG focused on the Enem Essay (REnem), carried out according to the assumptions of the ISD, can provide subsidies that promote the development of the language skills of EM students. The REnem genre was taken as the structuring genre of the PDG and the main reference for verifying the development of language skills. As specific objectives, it was established: a) to investigate and create a PDG through intervention research with EM students, in order to identify how this device can contribute to the development of language skills and language actions; b) produce the Didactic Genre Models (MDG) (Machado; Cristóvão, 2006) of the Ruled Debate, the REnem and the Informative Booklet, to understand their characteristics and establish the teachable dimensions based on the analysis of these genres; c) critically analyze the students' textual productions resulting from the PDG, to verify concrete linguistic evidence of the expansion of language capabilities; d) discuss the students' perceptions about the learning process experienced. This work is justified by the need to investigate interdisciplinary and collaborative methodological alternatives for teaching LP that improve, in addition to linguistic knowledge, argumentation and contribute to the formation of individuals who act in the world and interpret it in a socially conscious, responsible, literate and critical way. In addition, the study contributes to validating the potential of the PDG in relation to the teaching work for the promotion of integrated reading and writing in schools, in order to bring students closer to social language practices that are significant for their development as citizens. To this end, the investigation is characterized as intervention research, with data generated throughout the last quarter of 2023 in a state public school in Ijuí, RS. The corpus of analysis consisted of three essays written by 10 students - initial version, final version and rewrite (according to the nomenclature adopted in the PDG); by the production of an Information Booklet (Koch; Elias, 2019), planned and created by the class itself; and by the data from the feedback form completed by the class, where they were able to express their perceptions about the entire process. In general, the data were analyzed qualitatively in light of Bronckart's Textual Architecture (2006) and the ISD as a whole. The study revealed that the PDG can greatly promote the expansion of the participants' language capabilities, as well as the learning of specific REnem techniques and linguistic skills. It is evident that the ability to argue was enhanced, consequently developing the class's critical thinking on the social themes addressed. Therefore, an important piece of evidence was the contribution of the PDG to the development of literacy in the mother tongue. The research also highlighted limitations of the REnem genre, such as its structural standardization, which reinforces the perception that work with this genre cannot be mechanical and focused on writing training. Still, as the objectives were achieved, the thesis that a didactic-pedagogical practice, structured and applied through a PDG based on ISD, can offer tools to foster the development of students' language skills was supported throughout this study.